2013
DOI: 10.1021/ma401052x
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Deformation of Oriented Poly(ε-caprolactone) and Its Miscible Blends with Poly(vinyl methyl ether)

Abstract: The structural evolution of micro-molded poly(ε-caprolactone) (PCL) and its miscible blends with noncrystallizable poly(vinyl methyl ether) (PVME) at the nanoscale was investigated as a function of deformation ratio and blend composition using in situ synchrotron small-angle X-ray scattering (SAXS) and scanning SAXS techniques. It was found that the deformation mechanism of the oriented samples shows a general scheme for the process of tensile deformation: crystal block slips within the lamellae occur at small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…This principle ingeniously unified the very beginning 'slips within the lamellae including crystallographic fine slips and intralamellar mosaic block slips' stated by Peterlin et al [69e71] and 'stressinduced melting and recrystallization' insisted by Flory et al [72] during deformation of semi-crystalline polymers in early years. This principle has been proven to be true in isotropic polymers with spherulites and anisotropic samples with deformed spherulites [42,48,54,55,73]. There needs to be verified whether it is still applicable to the deformation of oriented polymers.…”
Section: Deformation Behavior Of Bsk Ippmentioning
confidence: 99%
See 2 more Smart Citations
“…This principle ingeniously unified the very beginning 'slips within the lamellae including crystallographic fine slips and intralamellar mosaic block slips' stated by Peterlin et al [69e71] and 'stressinduced melting and recrystallization' insisted by Flory et al [72] during deformation of semi-crystalline polymers in early years. This principle has been proven to be true in isotropic polymers with spherulites and anisotropic samples with deformed spherulites [42,48,54,55,73]. There needs to be verified whether it is still applicable to the deformation of oriented polymers.…”
Section: Deformation Behavior Of Bsk Ippmentioning
confidence: 99%
“…11 [11]. In general, a 4-point or even 6-point scattering feature can be expected to appear in the off-axis during the stretching of isotropic semi-crystalline polymers prior to finally concentrating in a 2-point scattering feature, which is thought to be caused by the oblique crystal orientation [68,73,75]. Even though it is reported that oblique crystal orientation usually gives rise to symmetric off-axis scattering [75], specifically, coarse slip of main lamellae.…”
Section: Deformation Behavior Of Bsk Ippmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the samples were not measured at one time, two conditions were applied. 1060 mm for sample-todetector distance and 60 min for exposure time were applied for samples with ε ¼ 0, 5,15,17,20,25,30, 110% as the final strains, while 1753 mm for sample-to-detector distance and 20 min for explosion time were applied for samples with ε ¼ 10, 40, 55, 70, 90, 135, 160% as the final strains. The scattering intensity distributions were not affected by these two conditions, while the affected intensities were not compared together.…”
Section: Two-dimensional Small-angle X-ray Scattering (2d-saxs)mentioning
confidence: 99%
“…20 The presence of functional groups in polymer chains, giving rise to specic interactions with the blend constituent, can enhance the interfacial adhesion and phase dispersion, and improve the overall characteristics of the systems.…”
Section: Introductionmentioning
confidence: 99%